Ações de urgência e emergência no Estado do Ceará: uma proposta de organização a partir da implantação do atendimento pré-hospitalar - Feitosa, Paulo Egidio dos Santos (2008)
This study, descriptive, aimed to develop a proposal for organizing the State System of Urgency and Emergency in the state of Ceará-Brazil, based on the deployment of the prehospital emergency care. Proposes the design of regional services in the optics of prehospital care with emphasis on the completeness of care and integration of services, qualification and the humanization of attention. Based on data from DATASUS and IBGE, year 2003, in conformity with a Minister of Health Order nº 2048/2003-GM-MS, were defined 12 regional clusters of urgency/emergency, with the same number of centrals regulation (11 to be implanted), 133 ambulances are needed for basic support (USB in portuguese) and 28 ambulances for advanced support (USA in portuguese). The necessary staff will be: 396 physicians, 396 nurses, 737 assistant/technical nursing, 660 ambulance drivers, 11 pharmacists, 110 telephone operators, among others. It was analyzed the admissions quantitative made in 20 poles hospitals in relation to the intervals of distance from the place of domicile. The occupation of beds is, in its majority, made by people of the municipality where the hospital is located. Based on the features of the Act Order of a Minister of Health nº 1101/GM-MS and according to the pole-regional grouping suggested, an analysis was made to verify the amount of beds available. It was obeyed that the number of beds is insufficient, more worrying is the situation of the ICU beds. As for the types of procedures of emergency, in the comparison between the poles, by frequency, there is greater focus on admissions for carrying out deliveries, cesarean sections and curettage post-abortion. It is suggested that the implementation of services should be done gradually with priority to the most underprivileged regions. In the re agreement of occupation of the beds in poleregional hospitals there should be clear a fair percentage for the types of procedures to be used by residents of the municipalities in regional coverage area, with definition of a standardized portfolio of hospital services, targeting self-sufficiency of emergency care at micro and macrorregional health in the state of Ceara.